IMPLEMENTASI PERENCANAAN PEMBANGUNAN DAERAH (Studi tentang Musrenbang di Kabupaten Sumenep) - Sidik, Soengkono (Universitas 17 Agustus 1945 Surabaya, 2016)
Regional Development Planning through Musrenbang a means to foster initiativeand active role in community development planning (Bottom Up Planning) aremechanically and functionally with activities planned development based on theprinciple of consensus, mobilize and improve the initiatives and participation ofthe community to carry out development in an integrated and foster the dynamicconditions of the community. This research method using a qualitative approach.Research carried out by focusing on two districts and three villages and thevillages and informants deliberately determined among the actors involved in theimplementation of planning forums. Of the several theories of implementation, thecombination approach better able to explain than the top-down, bottom-upapproach and the critical-creative approach. While the implementation modelMerilee Griddle (1980) combined with Elmore models more appropriate toanalyze the implementation of Musrenbang compared with models otherimplementations.Keywords: Implementation, Musrenbang, Public Participation